Ecology of Nepenthes clipeata on Gunung Kelam, Indonesian Borneo. (4th July 2021) - Mansur, Muhammad; Brearley, Francis Q.; Esseen, Philip J.; Rode-Margono, E. Johanna; Tarigan, M. Rafi'i Ma'arif
ABSTRACT: Background: Nepenthes clipeata is a Critically Endangered plant species with the population at its only location in the wild, Gunung (Mount) Kelam in Kalimantan, Indonesia, under threat – its nutrient relationships have not been studied. Aims: To improve understanding of the autecology of N. clipeata by assessing the current population and providing information on its mineral nutrient relationships. Methods: A survey was undertaken in 2019 when population numbers and habitat preferences of N. clipeata were recorded. Nutrient concentrations in soil, leaves and pitcher fluid were analysed and compared with those in other Nepenthes species. Results: Eighteen individuals of N. clipeata were found on Gunung Kelam (only one of which was female). Seven other Nepenthes species were found and hybrids with two of these and N. clipeata were observed. Although the foliar nutrient concentrations ('ionome') of N. clipeata appeared distinct from that of other Nepenthes species, with N. clipeata having greater nutrient concentrations, particularly nitrogen, potassium and calcium, nitrogen limitation was still prevalent. Conclusions: N. clipeata still persists in the wild but with very low numbers, indicating that conservation actions are required. Along with other species of Nepenthes, it is limited by soil nitrogen concentrations although it has a distinct ionome derived from high foliar nutrient concentrations.